Scalable Video Processing and Frame Analysis System for Automated Monitoring of Chicken Behavior Based on Artificial Intelligence Technologies - Svitlana Antoshchuk; Oleksii Danchuk; Tetiana Kunup (Proceedings of the International Conference on Applied Innovations in IT)
Modern global crises have significantly impacted the agribusiness sector, particularly poultry farming, which has experienced issues with logistics, labor shortages, and disruptions in the supply of feed and veterinary drugs. Under these conditions, the implementation of artificial intelligence (AI) has become a necessity to ensure production stability. The use of AI in poultry farming allows for the automation of monitoring processes, improves the management of poultry health, and reduces reliance on human resources, which is especially important amid the pandemic and quarantine measures. This article examines the benefits of automated systems for monitoring the condition of chickens, including methods for tracking both natural and sick behavior that allow for the timely detection of diseases and minimization of production risks. The use of digital technologies and AI helps adapt to changes in market demand and ensures higher resilience of enterprises in crisis situations. The article highlights the advantages of using automated systems to monitor chicken health under conditions of limited human resources. A software solution has been developed for monitoring chicken health, which enables video uploads from local sources or video services such as YouTube, selection of the communication language, and the LLM model. It provides a user-friendly interface for interacting with AI. The program consists of two components: the frontend and the server side. Interaction with the server side occurs via an API, allowing seamless integration into any interface. The software architecture ensures convenient scalability and functionality expansion through the addition of agents and services. Such innovative solutions hold great potential for the development of the agribusiness sector, contributing to increased efficiency and resilience to crisis situations.